2012
DOI: 10.1585/pfr.7.2405074
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Simultaneous H and D Permeation through Lithium-Lead

Abstract: Clarification of tritium transfer in blanket is an important issue for realizing fusion reactor. We perform an experiment of simultaneous H and D permeation through Li 17 Pb 83 by means of an unsteady permeation method in order to clarify the interactions and isotope effects between H and D atoms. The experiment is conducted under the condition where the Sieverts' law holds. As a result, it is found that (i) H and D atoms permeate independently regardless of the H/D component ratio in the upstream gas and (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Among the others, the transport properties of the hydrogen isotopes in breeders materials are of interest for the tritium control and confinement. In the last 20 years, a large work has been carried out in order to determine the tritium diffusivity and solubility in the Pb-Li alloys [1][2][3][4][5][6][7][8][9]. A recent review work reported the incoherence of the literature data about the hydrogen isotopes solubility [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the others, the transport properties of the hydrogen isotopes in breeders materials are of interest for the tritium control and confinement. In the last 20 years, a large work has been carried out in order to determine the tritium diffusivity and solubility in the Pb-Li alloys [1][2][3][4][5][6][7][8][9]. A recent review work reported the incoherence of the literature data about the hydrogen isotopes solubility [10].…”
Section: Introductionmentioning
confidence: 99%